ANALYSIS OF CLASS IV STUDENTS' DIFFICULTIES IN PERFORMING MANDATORY PRAYERS - Fuad Abdullah Fuad; Nuza Heri Setyani; Achmad Buchori; Joko Sulianto (Universitas PGRI Semarang, 2023)
Articles are created with the aim of describing students' difficulties; Factors responsible for the difficulties involved in salat; And the effort that can be made to overcome the students' difficulties of performing mandatory religious services. The type of research used is qualitative descriptive. Main data retrieval techniques using study literature study. The factors behind the student's difficulties in mandatory worship match the theory of sheikh abdul shuuja 'ahmad bin husein and the ahmadi and supriyono. The difficulties students experience in performing mandatory religious services need attention early and early teacher support, parental example at home before coming up with the interest of the students in performing mandatory services without any coercion. Research concludes that motivation, interest, interactive religious studies, school facilities and parental example require students to mandatory salat.